Separation processes in waste minimization - Long, Robert B. (Environmental science and pollution control, 1995)
This work offers an accessible discussion of current and emerging separation processes used for waste minimization, showing how the processes work on a day-to-day basis and providing troubleshooting tips for equipment that doesn't function according to design specifications. It describes the fundamentals of over 30 processes, types of equipment available, vendors, and common problems encountered in operations with hazardous waste.